Implementing Decision-Making Grid Model to Improve Maintenance Strategies in Oil Palm Industries - Emon Azriadi (Journal of Engineering Science and Technology Management, 2021)
A typical maintenance organisation has responsibility in keeping the production facility running at the desired level performance. In order to ensure that condition, necessary decisions should be made. The Decision Making Grid (DMG) model is one of analysis technique that provides maintenance organisation in strategic and tactical level management to determine the appropriate maintenance policy for all individual machinery and equipment within the facility. The analysis identified the performance of the equipment in oil palm mill facility by conducting availability measurement. The machineries and equipment which have breakdown records were analysed then by the DMG model to propose the appropriate maintenance policy for all individual machinery and equipment within the facility. Implementing the DMG recommendations were proposed to follow the suggested priority order.